Efficacy and Safety of Insulin Pump Therapy in Children and Adolescents with Type 1 Diabetes Mellitus - Millad Ghawil; Rania Issa; Safa Saed (AlQalam Journal of Medical and Applied Sciences, 2024)
Continuous subcutaneous insulin infusion (CSII) pump represents a treatment option that can aid in achieving an important goal to reduce the most frequent complications associated with treatment; hypoglycemic and hyperglycemic episodes, which have also a great impact on life quality of patients. This study was conducted to report the effect and safety of insulin pump therapy on glycemic control, hypoglycemia and diabetic ketosis (DKA) rates in Libyan type 1 diabetic (T1D) patients. A descriptive and retrospective study which included patients treated and followed up at Tripoli University Hospital. Fifty-seven T1D patients used CSII pump enrolled in this study. Assessment of hypoglycemia, DKA, measuring the glycosylated hemoglobin (HbAlc) values at time of diagnosis (prior to CSII) and at time of study conduction. Mean age was 12.72 year ± 3.8 SD. Mean duration of diabetes was 7.28 years ± 3.9 SD. The baseline mean HbA1c was 8.58 ± 1.73% during Multiple Daily Injections (MDI) at pre-pump and 7.76 ± 1.33% post initiation of CSII (p = 0.001), with higher proportion of patient’s post-pump treated had good metabolic control with HbA1c compared to pre-pump infusion 23, 40.4% and 16, 28.1%, respectively. Both the incidence of ketoacidosis and severe hypoglycemic episodes was improved compared with MDI pre-pump significantly during CSII (P<0.001). This study supports that CSII is an effective alternative in managing T1DM. In addition, therapy with insulin pump in children with diabetes is very efficient and safe with obvious reduction of HbA1c and significantly diminished rates of DKA and hypoglycemia. هي دراسة وصفية واسترجاعية شملت المرضى الذين يتم علاجهم ومتابعتهم في قسم الأطفال بمستشفى طرابلس الجامعي. سبعة وخمسون مريضاً من مرضى T1D والمستخدمين لمضخة الانسولين مسجلين في هذه الدراسة. وتتضمن الدراسة تقييم نوبات انخفاض مستوي السكر (الجلوكوز) في الدم ،معدلات حدوث الحماض الكيتوني السكري DKA، وقياس قيم الهيموجلوبين السكري الغليكوزيلاتي (HbAlc) في وقت التشخيص قبل استخدام مضخة الانسولين وفي وقت إجراء الدراسة. كان متوسط العمر 12.72 سنة ± 3.8 SD ومتوسط مدة الإصابة بمرض الداء السكري كان 7.28 سنة ± 3.9 SD ، كان متوسط الهيموجلوبين السكري الغليكوزيلاتي HbA1c هو 8.58 ± 1.73٪ أثناء فترة العلاج بالحقن اليومي المتعدد (MDI) في مرحلة ما قبل استخدام المضخة و7.76 ± 1.33٪ بعد العلاج بمضخة الانسولين CSII (P =0.001)، مع وجود نسبة أعلى من المرضي الذين تم علاجهم بالمضخة كان لديهم تحكم في الداء السكري جيد مع HbA1c مقارنة بنوع العلاج قبل استخدام مضخة النسولين 23- 40.4% و 16- 28.1%، على التوالي. معا معدلات حدوث الحماض الكيتوني السكري والنوبات الشديدة في انخفاض مستوي السكر (الجلوكوز) في الدم تحسنت بصورة كبيرة بالعلاج بمضخة الانسولين CSII مقارنة مع فترة العلاج بالحقن اليومي المتعدد(MDI) P <0.001. تدعم هذه الدراسة أن استخدام مضخة النسولين CSII هو بديل فعال في علاج النوع الأول من الداء السكري T1DM، بالإضافة لذلك فإن العلاج بمضخة الأنسولين للأطفال المصابين بداء السكري فعال وآمن للغاية مع انخفاض واضح في نسبة الهيموجلوبين السكري الغليكوزيلاتي HbA1c وانخفاض كبير في معدلات حدوث الحماض الكيتوني السكري وفي حدوث نوبات انخفاض مستوي السكر (الجلوكوز) في الدم.